Defective nanomaterials for electrocatalysis oxygen reduction reaction - Mao, Zhanxin; Tang, Xianyi; An, Xuguang; Jiang, Jinxia (Frontiers in Chemistry, 2022)
The difficulties in O2 molecules adsorption/activation, the cleavage of the O-O bond and the desorption of the reaction intermediates at the surface of the electrodes make the cathodic oxygen reduction reaction (ORR) for fuel cells extremely sluggish kinetics. Thus, it is important to the exploitation of highly active and stable electrocatalysts for ORR to promote the performance and commercialization of fuel cells. Many studies have found that the defects affect the electron and geometrical structure of the catalyst. The catalytic performance is enhanced by constructing defects to optimize the adsorption energy of substrates or intermediates. Unfortunately, still many issues are poorly recognized, such as the effect of defects (types, contents, and locations) in catalytic performance is uncleared, and the catalytic mechanism of defective nanomaterials is lacking. In this review, the defective electrocatalysts divided into noble and non-noble metals for ORR are highlighted and summarized. With the assistance of experimental results and theoretical calculations, the structure-activity relationships between defect engineering and catalytic performance have been clarified. Finally, after a deeper understanding of defect engineering, rational design efficient and robust ORR catalysts for PEMFCs is further guided.